Gene Knockouts Reveal Separate Functions for Two Cytoplasmic Dyneins in Tetrahymena thermophila - Lee, Seungwon (The American Society for Cell Biology, 1999)
In many organisms, there are multiple isoforms of cytoplasmic dynein heavy chains, and division of labor among the isoforms would provide a mechanism to regulate dynein function. The targeted disruption of somatic genes in Tetrahymena thermophila presents the opportunity to determine the contributions of individual dynein isoforms in a single cell that expresses multiple dynein heavy chain genes. Substantial portions of two Tetrahymena cytoplasmic dynein heavy chain genes were cloned, and their motor domains were sequenced. Tetrahymena DYH1 encodes the ubiquitous cytoplasmic dynein Dyh1, and DYH2 encodes a second cytoplasmic dynein isoform, Dyh2. The disruption of DYH1, but not DYH2, resulted in cells with two detectable defects: 1) phagocytic activity was inhibited, and 2) the cells failed to distribute their chromosomes correctly during micronuclear mitosis. In contrast, the disruption of DYH2 resulted in a loss of regulation of cell size and cell shape and in the apparent inability of the cells to repair their cortical cytoskeletons. We conclude that the two dyneins perform separate tasks in Tetrahymena.